PENGARUH MODEL PEMBELAJARAN INQUIRY BERBANTUAN MEDIA VIDEO TERHADAP HASIL BELAJAR IPAS SISWA KELAS 4 SDN 6 SINGKAWANG - Nur Azza Ananda; Rini Setyowati; Emi Sulistri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Azza: The Influence of the Inquiry Learning Model Assisted by Video Media on theScience and Science Learning Outcomes of Class IV Students at SDN 6Singkawang. Thesis, ISBI Singkawang, 2024.This research aims to determine whether there are differences, improvements andthe influence of using the Inquiry model assisted by video media on the science andscience cognitive learning outcomes of class IV students at SDN 6 Singkawang.The type of research used is quantitative research using the Quasi ExperimentDesign method with a Nonequivalent Control Group Design design. The samplestaken in the research were 18 class IVA students. The data collection techniqueuses an essay test technique containing cognitive domain indicators. The dataanalysis technique uses a two-sample t-test and effect size. The results of thisresearch are: 1) there is a significant difference between the cognitive learningoutcomes of students who are given an inquiry model assisted by video media andclasses that use a direct learning model. based on the results of the t test calculationof two samples t_count > t_table, namely 3.5361 > 2.042, which means that thereare differences in students' science and science cognitive learning outcomesbetween the experimental and control classes, 2) there is an increase in students'science and science cognitive learning outcomes in classes that use the assistedinquiry model video media with N-Gain results with an average of 0.59 with apercentage of 59% in the medium category, 3) the Inquiry model assisted by videomedia has a high influence on the science and science cognitive learning outcomesof class IV students at SDN 6 Singkawang. This can be seen from the calculation ofthe effect size, namely 1.18 and the criteria are high, 1.18 is at E_S > 0.80.